El estatus categorial de "puros" prenominal: un determinante improbable - Vázquez Rojas Maldonado, Violeta (El Colegio de México, 2015)
In Mexican Spanish, noun phrases introduced by the prenominal adjective puros –roughly equivalent to only– behave like bare nouns, but they also have the distribution of determiner phrases. If it is a determiner, puros is peculiar, because its syntactic complement does not correspond to its semantic restrictor. In other words, it would be a non-conservative determiner, thus violating a semantic universal. In this paper I propose an analysis of puros as an adjectival modifier, and I argue that this analysis can be applied to other expressions that have been identified crosslinguistically as possible non-conservative determiners.